Chloride diffusion behavior and microstructure of basalt-polypropylene hybrid fiber reinforced concrete in salt spray environment. (21st March 2022) - Su, Li; Niu, Ditao; Huang, Daguan; Luo, Yang; Qiao, Hongxia; Zhang, Yunsheng
Highlights: The pore solution pH and chloride concentration of BPHFRC after salt spray erosion were studied. A calculation model of apparent chloride diffusion coefficient was proposed. The addition of fibers could inhibit the deterioration of pore structure in the process of erosion. With the increase of erosion time, the bond strength between fibers and concrete matrix decreased. Abstract: The chloride diffusion performances of basalt-polypropylene hybrid fiber reinforced concrete (BPHFRC) in salt spray environment were investigated. The effects of concrete strength, fiber addition form and content on the pore solution pH and chloride concentration were evaluated. The results showed that the stable depth of pore solution pH of BPHFRC increased with the increase of exposure time. The greater the strength of concrete, the slower the decrease rate of pore solution pH with exposure time. The effects of addition form and content of basalt fiber (BF) and polypropylene fiber (PF) on chloride concentration were different. When the fiber content was 0.1%, the addition of BF, PF or hybrid BF-PF could improve the chloride corrosion resistance of concrete. However, addition of 0.2% hybrid BF-PF increased the chloride concentration in the concrete. The apparent chloride diffusion coefficient of BPHFRC decreased with an increase of salt spray erosion time, and exhibited a power function with erosion time. The calculation model of BPHFRC apparent chloride diffusion coefficient was established, and its effectiveness was verified. In addition, the pore structure, phase composition and micromorphology of BPHFRC before and after erosion were performed using RapidAir-457 porosity analyzer, X-ray diffraction and field emission scanning electron microscope, and the influence rules of BF and PF on chloride diffusion properties of concrete was discussed.